EXPONENTIAL STABILITY CONTROL FOR NETWORKED SYSTEMS WITH INTERVAL DISTRIBUTION TIME DELAYS - Hejun; Fushun (Acta Informatica Malaysia, 2018)
To study the problem of exponential stability control for a class of networked control systems with interval distribution time delays, a new approach is given to model the networked control systems with the stochastic time delays which is assumed to be satisfying a interval Bernoulli distribution. Based on linear matrix inequality approach, the mean-square exponential stability controller design method is presented, and the controller gain matrix is obtain by solving a linear matrix inequality. Moreover, a Lyapunov functional is used, and some stack matrices, which bring much flexibility in solving LMI, are introduced during the proof. A numerical example is given to demonstrate the validity of the results.